PENERAPAN METODE MEASUREMENT SYSTEM ANALYSIS GAGE R&R PADA PENGUKURAN PRODUK BASE PLATE MAGAZINE - Albertus Laurensius Setyabudhi; Okta Veza; Delia Meldra; Nandar Cundara Abdurahman; Muhammad Rizki Reza Saputra (JURNAL REKAYASA SISTEM INDUSTRI, 2021)
In the current era of globalization, the perceived quality competition globally is manufacturing. Manufacture industry competition makes companies must concentrate on product quality. and the quality of the factors affecting the product is wrong, such as human resources, tools / machines, and the environment can also cause product quality. And one of the companies engaged in the manufacturing industry, namely PT. APT has a problem with the quality measurement of the dimensions of size on one of the products made, where the product can’t be accepted by the customer and declared reject on all the number of products sent. There are indications of QC checking errors within the company so that reject products are accepted as acceptable. The purpose of this research is to find out what are the main causes of goods declared acceptable internally within the company and when it arrives at the customer is declared reject. And find solutions to how such mistakes do not happen again. To solve this problem, this study uses the MSA (Measurement System Analysis Gage R&R) method which has the advantage of knowing the cause of quality problems in detail whether from the people, tools, or supporting factors in a measurement. So that mistakes that occur before do not happen again and the company can run more effectively, efficiently and consistently in measuring and checking.